"GREEN CHEMISTRY" AND INNOVATIVE MATERIALS: ENVIRONMENTALLY SAFE PRODUCTS - BASHLAI, SERHII; REZNICHENKO, VITA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article examines the role of "green chemistry" in sustainable development, especially in the field of agriculture, in the context of global competition and resource limitations. The purpose of the research is to analyze the impact of "green chemistry" and the use of innovative materials on the development of safe and environmentally friendly products in agriculture. The authors analyze how sustainability and sustainable development are becoming important requirements for modern business, focusing on the balance between environmental protection and safe production of products. The processes of integrating the concepts of "green chemistry" into the development of safe and environmentally friendly products, which occurs at the level of molecular design and the use of safe chemical processes, were defined. The introduction of innovative materials that contribute to the creation of products and processes with a minimal impact on the environment, in particular with the help of non-toxic and renewable resources, has been studied. Measures for the development of new green catalysts and methods that ensure the efficiency of atoms and the use of safe solvents are substantiated. The practical application of the principles of "green chemistry" in the agrochemical industry has been formed, which contributes to the reduction of the use of harmful chemicals and pesticides. The importance of "green chemistry" in agriculture is emphasized, particularly in the context of low-cost, zero-waste food production. An analysis of the impact of modern farming methods on the emission of greenhouse gases and the development of strategies to reduce this impact with the help of "green chemistry" was carried out. An assessment of the impact of improper use of pesticides on the contamination of agrochemical fields and the implementation of alternative approaches, in particular organic farming, is provided. Identified aspects reflecting a comprehensive approach to solving the problems of environmental safety and sustainable development with the help of "green" chemistry, which is innovative in the context of modern agriculture. The research is focused on identifying ways in which "green chemistry" can contribute to the creation of products that minimize harm to the environment and human health.
Keywords: "green" chemistry; "green" synthesis; ecological agricultural activity; toxic substances; ecologically safe products; pesticide-free technology